Model for estimation of global solar radiation in Sarawak, Malaysia - Jakhrani, A.Q.; Othman, A.K.; Rigit, A.R.H.; Samo, S.R. (IDOSI Publication, 2011)
The aim of this work was to estimate the obtainable amount of global solar radiation for the development of solar photovoltaic power systems at four locations namely Sri Aman, Sibu, Bintulu and Limbang in Sarawak, Malaysia.